Faktor Kinerja yang Menyebabkan Diskrepansi Diagnosa Awal Dokter IGD dengan Diagnosa Akhir Dokter Spesialis dalam Mendiagnosa Penyakit Paru di RSU Mitra Medika Bandar Klippa - Lucyana Lucyana; Arifah Devi Fitriani; Ramadhani Syafitri (Jurnal Riset Hesti Medan, 2025)
Lung disease is a disease characterized by persistent respiratory disorders and limitations caused by abnormalities of the airways or alveolar tract due to exposure to harmful particles and gases. RSU ER. Mitra Medika Bandar Klippa has certain indicators to maintain quality and patient safety, in this case the indicator is the Accuracy of Diagnosis of Priority Lung Diseases by Emergency Room Doctors. The number of priority lung patients from May - November 2021 was 1,309 patients and the number of correct diagnoses was 928 patients, the remaining 381 patients received incorrect diagnoses. The aim of this research is to analyze the performance factors that cause discrepancies in the initial diagnoses of emergency room doctors and the final diagnoses of specialist doctors in diagnosing priority lung diseases. This type of research uses a qualitative method with a descriptive approach which was carried out in August – September 2022, with a total of 8 informants, 2 (two) people namely Specialist Doctors, namely 5 (five) emergency room doctors, 1 (one) person namely Service Manager Patient (MPP) at RSU. Klippa Bandar Medika Partners. From the results of the research and discussion, it was concluded that from the performance factors (Work Quantity, Knowledge, Cooperation and Work Initiative) only 2 (two) performance factors caused a discrepancy in the initial diagnosis of the ER doctor and the final diagnosis of the Lung Specialist Doctor, namely, Work Quantity and Knowledge. Based on the research results, it is recommended to RSU Management. Mitra Medika Bandar Klippa needs to propose training related to lung disease for all General Practitioners who work at RSU. Klippa Bandar Medika Partners.